Analysis Of School Operational Assistance Fund Management Based On Application At SMKN 4 Soppeng - Asmi Rahayu; Nur Achriaty Achmar; Muh. Aqsha Hasri (GENTARA: management and accounting research, 2026)
The management of educational funds is a crucial aspect in supporting the continuity of teaching and learning processes at schools. One form of government support in the education sector is the School Operational Assistance (BOS) program, which aims to finance non-personnel operational needs. However, in practice, the management of BOS funds often encounters administrative and technical obstacles, particularly related to reporting and transparency. Therefore, the government has developed the ARKAS application as a digital tool to facilitate the planning, implementation, and reporting of BOS fund usage. SMKN 4 Soppeng, as one of the BOS fund recipients, also implements this application, but the extent of its effectiveness and efficiency still requires further study. This research aims to analyze the application-based management of BOS funds at SMKN 4 Soppeng, focusing on three main aspects: planning and budgeting, implementation and administration, as well as reporting and accountability of BOS funds. The method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects include the principal, treasurer, application operators, and parents, selected to comprehensively explore information regarding the implementation of the ARKAS application in school fund management. The results show that the management of BOS funds at SMKN 4 Soppeng generally follows applicable procedures and regulations. The planning process involves all school elements and is systematically recorded in the ARKAS application. Budget execution is supported by the e-BKU and SIPLah systems to facilitate bookkeeping and procurement. However, challenges such as limited infrastructure and technical understanding of the application remain obstacles. Therefore, it is recommended that the school and government provide continuous training for educational staff and improve technological facilities to support more effective and accountable fund management